Production of nitrate spikes in a model of ammonium biodegradation - Moyles, I; Fowler, A (Springer Netherlands, 2018)
Nitrification at the site of a contaminant ammonium plume from a former coal carbonisation plant can be modelled with three competing bacterial populations of Nitrosomonas, Nitrobacter, and Brocadia anammoxidans. Oscillations of chemical species at the site can be explained by a reduced model of ammonium competition between Nitrosomonas and B. anammoxidans which effectively acts as an activator-inhibitor system. Stable oscillations occur in conditions of low nutrient (ammonium) supply and this causes a spatial travelling wave in a borehole profile when diffusion is introduced.